Modelmaking : a basic guide - Sutherland, Martha (W. W. Norton, 1999)
"Modelmaking is an introduction to the craft for students of architecture; landscape architecture; urban, interior, and theatrical design; or anyone who has the need or desire to make the large small. It shows you how toconstruct both study and presentation models using common materials such as paper, chipboard, illustration board, foamcore, balsa, and basswood. Concise instructions are supplemented by nearly 200 charming, easy-to-follow drawings. Learn how to choose the right materials for the job; make a base to support your model; render contoured sites; and fashion models of trees, people, and other entourage. To pique your interest, imaginative illustrations show how to capture the essence of modern architecture as well as classical forms, including columns,pediments, and friezes."--BOOK JACKET